Clinical Value of Pleural Effusion and Serum MMP-3 and CYFRA21-1 Combined with ADA in Differential Diagnosis of Pleural Exudative Effusion - Zhiyang Xu; Jun Guan; Jianxin Xu; Jiahua Tu; Jiangdong Cheng (Emergency Medicine International)
Objective. The aim of the study is to investigate the clinical value of matrix metalloproteinases-3 (MMP-3) and cytokeratin 19 fragment antigen 21-1 (CYFRA21-1) combined with adenosine deaminase (ADA) in pleural effusion and serum in benign and malignant pleural exudative effusion (PEE). Methods. A total of 119 adult patients with PEE admitted in our hospital from May 2018 to October 2021 were selected. According to the patient’s condition, the patients were divided into the benign group (n = 75) and the malignant group (n = 44). The levels of MMP-3, CYFRA21-1, and ADA in pleural effusion and serum were detected. The receiver operating characteristic (ROC) curve was used to analyze the individual and combined predictive value of MMP-3, CYFRA21-1, and ADA levels. Results. In the malignant group, the pleural effusion and serum MMP-3 and CYFRA21-1 levels were higher than those in the benign group and the ADA levels were lower than those in the benign group (P < 0.05). In the malignant group, the positive detection rate of pleural effusion and serum MMP-3 and CYFRA21-1 was higher than that in the benign group and the positive detection rate of pleural effusion and serum ADA were lower than that in the benign group (P < 0.05). The AUC of pleural effusion MMP-3, serum MMP-3 and the combination of them in the diagnosis of PEE were 0.764, 0.722 and 0.810, respectively. The AUC of pleural effusion CYFRA21-1 and serum CYFRA21-1 and combination of them in the diagnosis of PEE were 0.776, 0.748 and 0.822, respectively. The AUC of pleural effusion ADA, serum ADA and their combination in differential diagnosis of PEE were 0.762, 0.737 and 0.836, respectively. The AUC of pleural effusion and serum of MMP-3 and CYFRA21-1 combined with ADA for differential diagnosis of PEE was 0.923. Conclusions. The diagnostic efficacy of MMP-3 combined with CYFRA21-1 and ADA in pleural effusion and serum for benign and malignant PEE are better than single index, which has certain clinical values for the selection of early intervention scheme for PEE patients.